PATTERN OF ALCOHOLISM AND CONSEQUENCES AMONG POPULATION - Kshirsagar, Sharad.V.; Tembe, Dinesh Tembe; Mangot, Ajish (International Journal of Psychosocial Rehabilitation, 2020)
It’s a well-known fact that consumption of alcohol in India is increasing day by day. More than half of the drinkers are heavy drinkers and stringent action must be taken against them. Various strategies have been implied by the government to control sales and pricing of alcohol, but these things haven’t improvised the situation. The aim of this investigation was to find the Pattern of alcoholism and consequences among population This cross-sectional study was conducted amongst males >18 years of age.210 study participants were selected by simple random sampling. 81 participants consumed alcohol. The pattern of alcohol consumption and its side effects were identified by a pre-tested structured questionnaire and Alcohol Use Disorders Identification Test (AUDIT). Data entry and analysis was done using Statistical Package for Social Sciences (SPSS) version 15 software. Descriptive statistics were calculated for background variables and the prevalence of the alcoholism. Chi-square test and p-value were calculated to see the association between alcoholism and social factors.A total of 210 adult male were enrolled in the study. Amongst 201 participant’s alcohol was consumed by 81 participants. The prevalence of alcohol consumption was 38.57%. Amongst 81 drinkers 52(64.19%) had problematic drinking pattern with 60(74.07%) had a hazardous/harmful drinking pattern and 21 (25.92%) were dependent alcoholics. The health issues related to alcohol consumption were hypertension, gastritis/peptic ulcer disease, and psychiatric illnesses.All the drinkers present in the area needs to be screened for their drinking pattern and other additional services like communication with the drinker and his family, health promotion and behavioural change should also be taken into consideration. Along with the alcohol consumer, this awful habit also affects the family.